PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DISERTAI PHET SIMULATION TERHADAP KETERAMPILAN PROSES SAINS DAN KEMAMPUAN PEMECAHAN MASALAH FISIKA DI SMA POKOK BAHASAN SUHU DAN KALOR - Sri Ayu Lestari; Bambang Supriadi; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2022)
The aims of this research were to investigate : (1) the influence of PBL model with PhET simulation to student’s science process skill’s; (2) the influence of PBL model with PhET simulation to student’s problem solving skill’s. this research used experimental research method. The sample of this student’s of slass XI IPA at MA Negeri 2 Jember. The data were collected by observation, documentation, and interview. The data was analyzed using the Independent sample t-test toshow the different between experiment class and control class. The results of the research were as follows: (1) PBL model with PhET simulation influence on science process skill’s of student’s (2) PBL model with PhET simulation influence on problem solving skill’s of student’s. Keywords: Problem Based Learning, science process sklill, problem solving skill.